Leflunomide and Polyomavirus-Associated Nephropathy in Renal Transplant - Ferreira, AC (2009)
Polyomavirus nephropathy is a major complication in renal transplantation, associated with renal allograft loss in 14 to 80% of cases. There is no established treatment, although improvement has been reported with a variety of approaches. The authors report two cases of polyomavirus infection in renal allograft recipients. In the first case, a stable patient presented with deterioration of renal function, worsening hypertension and weight gain following removal of ureteral stent placed routinely at the time of surgery. Ultrasound examination and radiology studies revealed hydronephrosis due to ureteral stenosis. A new ureteral stent was placed, but renal function did not improve. Urinary cytology revealed the presence of decoy cells and polyomavirus was detected in blood and urine by qualitative polymerase chain reaction. Renal biopsy findings were consistent with polyomavirus -associated nephropathy. In the second case, leucopaenia was detected in an asymptomatic patient 6 months after transplantation. Mycophenolate mophetil dosage was reduced but renal allograft function deteriorated, and a kidney biopsy revealed polyomavirus -associated nephropathy, also with SV40 positive cells. In both patients immunosuppression with tacrolimus was reduced, mycophenolate mophetil stopped and intravenous immune globulin plus ciprofloxacin started. As renal function continued to deteriorate, therapy with leflunomide (40 mg/day) was associated and maintained during 5 and 3 months respectively. In the first patient, renal function stabilised within one month of starting leflunomide and polymerase chain reaction was negative for polyomavirus after 5 months. A repeated allograft biopsy 6 months later showed no evidence of polyomavirus nephropathy. In the second patient, polyomavirus was undetectable in blood and urine by polymerase chain reaction after 3 months of leflunomide treatment, with no evidence of polyomavirus infection in a repeated biopsy 6 months after beginning treatment.